Analysis of the Influence of Media Exposure and Consumer Awareness Level on McDonald's Purchase Decisions During the Boycott Movement in Pekanbaru - Pamela Aisya Feliatra; Lailan Tawila Berampu; Rendra Wasnury (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of media exposure and consumer awareness on purchasing decisions of McDonald's during the boycott movement in Pekanbaru. A quantitative approach with a survey method was conducted among 146 respondents who had purchased McDonald's products and were aware of the boycott movement. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. The findings reveal that both media exposure and the boycott movement significantly and positively affect purchasing decisions. Media exposure and boycott movements also significantly influence consumer awareness. Meanwhile, consumer awareness has a negative impact on purchasing decisions and mediates the relationship between media exposure, boycott movements, and purchasing decisions. The model explains 60.7% of the variance in consumer purchasing decisions in Pekanbaru. These results highlight that purchasing decisions are not only influenced by rational factors but also by moral awareness and social solidarity. This study contributes to the literature on ethical consumer behavior and provides practical implications for companies in formulating communication strategies amid boycott issues.